A study of some aspects of the life and works of Abraham De Smidt (1829-1908) surveyor-general of the Cape Colony, with particular reference to the Cape Fine Arts Exhibitions between 1851 and 1890 - Bull, Marjorie (Michaelis School of Fine Art, 2016)
BIbliography: p. 151-154a.